Literature Study of Pasang Ri Kajang as a Guideline for Resolving Customary Violations in the Ammatoa Kajang Customary Law Community - Kurnia Ali Syarif (Cita konsultindo, 2022)
The Ammatoa indigenous people of the Kajang tribe have a cultural institution called. They live exclusively in the Area known as the Ammatoa Customary Area. The distances from the sub-district capital, regency capital and provincial capital to the location of customary areas are: 25 km, 57 km and 270 km respectively. The life of the indigenous people who live in the customary area is called the Ilalang embayyah (Kajang Dalam) area where the indigenous people adhere to or are guided by